The Effects of Blood Flow Restriction Training on Strength and Function During Early Rehabilitation After Anterior Cruciate Ligament Reconstruction in Adolescents. Issue 5 (31st May 2022) - Giampetruzzi, Nicholas; Fredericks, Arthur; Roman, Dylan; Prue, Jennifer; Lolic, Adel; Pace, Lee; Crepeau, Allison; Weaver, Adam
Background: Blood flow restriction training (BFRT) has gained popularity due to reported benefits in reducing muscle atrophy and mitigating strength deficits following anterior cruciate ligament reconstruction (ACLR). While there are a number studies that have reported on the use of BFRT in the adult population, there is limited information about the use of BFRT in the adolescent population and its effect on muscle strength and function. Hypothesis/purpose: The purpose of this study was to determine the effect of adding BFRT to traditional rehabilitation in the adolescent population after ACLR. This study's primary aim was to investigate the impact BFRT has on isometric strength testing and patient reported function at 3 months post-operatively. Methods: A prospective intervention group was compared to an age matched retrospective control group as part of an ongoing clinical trial. This included patients between 12 and 18 years of age, who underwent primary ACLR at Connecticut Children's from January 2020 to present. In addition to a standardized rehabilitation protocol these patients utilized a personalized tourniquet system for BFRT with limb occlusion pressure of 80%. A standardized BFRT protocol was followed over initial 12 weeks, completing 3 BFRT exercises per session. Load progression was based on the patient's perceived level of exertion. A three month strength assessment was completed by patients in both groups. The test included isometric knee extension and flexion strength at 60° of knee flexion. Peak torque was normalized to body weight and used to calculate limb symmetry index (LSI). IKDC scores were recorded. Two-sample t tests were used to determine differences between the BFRT and control groups. Results: The BFRT group consisted of 11 patients (6 females; 14.9 ± 1.8 years old). The control group consisted of 47 patients (24 females; 15.2 ± 0.6 years old). Age, height, and weight were not significantly different between groups (Table 1). Significant differences were seen between the BFRT and control groups for peak knee extensor torque when normalized to body weight in both the surgical (1.8 ± 0.4 vs 1.4 ± 0.6 Nm/kg, p=0.02) and nonsurgical limbs (2.7 ± 0.6 vs 2.1 ± 0.5 Nm/kg, p=0.03) (Table 2). No significant differences were seen between groups for knee extensor or flexor LSI or IKDC scores (Table 2). Conclusions: In adolescents, BFRT may impact bilateral knee extensor force production during early post-operative ACLR rehabilitation. Continued investigation is needed to further evaluate the impact of BFRT in this population. Table 1. Patient Demographics Table 2. Isometric Strength Tests and IKDC